Causes, factors, and complications associated with hospital admissions among patients with Parkinson's disease - Shaibdat, Navena Sharma; Ahmad, Norfazilah; Azmin, Shahrul; Ibrahim, Norlinah Mohamed (Frontiers in Neurology, 2023)
Introduction Patients with Parkinson’s disease (PD) are at a higher risk of hospital admissions compared to the general population. We studied the causes and factors associated with admissions among PD patients over six-years. Methods We included all PD admissions between 1st January 2016 to 31st December 2021. Other causes of parkinsonism were excluded. Causes of admissions were divided into PD-related (direct or indirect) or non-PD related. Type of admission was categorised into emergency or elective. Results We identified 605 hospital admissions (259 PD patients); 345 (57.0%) were PD-related and 260 (43%) were non-PD related. Emergency PD admissions contributed to 50.4% of all admissions; most commonly from respiratory infection (23%). PD admissions in comparison to non-PD admissions were associated with worse disease severity (HY ≥ 3); p<0.001, longer disease duration (8.71(SD 6.23) vs 6.60 (SD 5.39) years); p<0.001 and longer hospital stay (7.70 (SD 5.89) vs 6.42(SD 7.63) days); p= 0.020. Non-PD admissions were associated with more comorbidities (97.3%); p=0.013. There were 124 (20.5%) complications and 31 deaths (5.1%). 29 deaths were due to respiratory infection and 3 deaths were due to COVID-19 pneumonia. Emergency admission (PD and non-PD related); p=0.001 and respiratory related causes; p<0.001 were predictors of unfavourable hospital admission outcomes (death and complications). Conclusion Respiratory infection was the leading cause of hospital admission and independent significant predictor of unfavourable hospital admission outcome (death and complications). PD-related admissions were associated with disease severity, led to more complications and longer hospital stay. Non-PD related admissions were associated with comorbidities.